The Importance Of Investment Strategy In The Development Of Enterprise Activities (Eurasian Research Bulletin, 2024)
The article examines the role and significance of an investment strategy in the development of an enterprise's activities, analyzes the principles of forming an enterprise's investment strategy, and examines conclusions and recommendations based on international experience.